Economic burden for Alzheimer's disease in China from 2010 to 2050: a modelling study - Emilie Clay; Junwen Zhou; Zhan-Miao Yi; Suodi Zhai; Mondher Toumi (Taylor & Francis Group, 2019)
Objectives: We aimed to conduct a modelling study to estimate and predict the economic burden of AD to support the healthcare management of AD in China. Methods: The economic burden of AD was estimated with an evaluation of the prevalence of AD patients and a simulation of annual resource use and cost per AD patient in China using a published model. Percentage of AD patients being treated was assumed to be 5% from 2010 to 2050, with three scenarios testing the value of this parameter of 10%, 20% and 40% throughout 2020 to 2050. Results: The costs of AD were estimated to be from around 91 billion RMB in 2010 to 332 billion in 2050. Most of the current burden was related to private caregivers paid by families. With the percentage of patients being treated changing from 5% to 40%, costs were estimated to double. This was related to more hospitalisations and more use of care facilities, while the burden for families would decrease. Conclusion: A high economic burden related to AD is predicted. The burden would be driven mainly by indirect costs related to the social support of the patients. Investment in improving awareness and care of AD patients is needed and worth it.